New visible light excitable donor–acceptor 7-hydroxy-coumarins as blue fluorescent probes for selective staining of vacuoles in yeasts and L. donovani. Issue 14 (13th March 2017) - Raghuvanshi, Ashutosh; Kumar Jha, Ajay; Kathuria, Manoj; Priya Awasthi, Bhanu; Purohit, Deepak; Mitra, Kalyan; Goel, Atul
Abstract : New 3-cyano-7-hydroxy-4-methylthio-coumarins (CHMC s) were discovered as blue fluorescent probes for staining vacuoles. Abstract : In order to address the existing limitations of the commercially available fluorescent probe CMAC (7-amino-4-chloromethylcoumarin), a new series of highly fluorescent donor–acceptor 7-hydroxy-coumarin derivatives was prepared and these derivatives were used as vacuole specific fluorescent probes for live cell imaging of unicellular parasitic protozoa L. donovani promastigotes and yeast cells S. pombe and S. cerevisiae . The synthesized 7-hydroxy-coumarins exhibited interesting photophysical properties and have advantages such as excitation in the visible region, good water solubility, photo-stability, good quantum yield and low cytotoxicity.